ANALYSIS OF THE EFFECTIVENESS OF LEASING FINANCING IN IMPROVING ACCESS TO CAPITAL FOR MICRO AND SMALL ENTERPRISES - Hidayu, Seri; Hendra, Joni; Ansori, Ridho; Mulyana, Sherly; Salsabila, Elsa; Wahyuni, Sri Rahayu; Virgiawan, Teguh (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Sharia leasing provides an asset-based financing mechanism that enables Micro and Small Enterprises (MSEs) to obtain productive equipment without requiring substantial upfront capital. This study analyzes the effectiveness of sharia leasing, particularly the ijarah and ijarah muntahiyah bittamlik (IMBT) contracts, in improving MSEs’ access to capital. Using literature review methods, this study evaluates scholarly articles, books, and regulatory documents related to Islamic financing. The findings indicate that sharia leasing effectively enhances access to capital because it does not require additional collateral, offers flexible payment structures, and includes asset ownership options at the end of the lease period. However, its implementation faces challenges such as limited sharia leasing institutions, low financial literacy, and insufficient product innovation. Strengthening education, expanding institutional reach, and developing more flexible leasing models are needed to maximize its contribution to MSE development.